PENGARUH MARKETING MIX TERHADAP PENJUALAN PADA INDUSTRI MANUFAKTUR PT. DWISELARAS JAYAPACK - Rina Angelina; Yosi Stefhani (Pasca Sarjana Universitas Satya Negara Indonesia, 2022)
In achieving marketing goals, of course using marketing tools, the marketing mix (Marketing Mix) which has a strong influence on prices, products, people, processes, promotions, physical evidence and also place.PT. Dwiselaras Jayapack is a printing manufacturing industry, producing raw goods into finished goods using tools, equipment, machines, on a large scale. This study aims to analyze the effect of Marketing Mix on sales in the manufacturing industry of PT. Dwiselaras Jayapack. This research is a quantitative causal research that aims to determine the relationship between two or more variables. The population and sample of this research are consumers of PT. Dwiselaras Jayapack, totaling 58 consumers, consisting of companies represented by the marketing department and individuals. Data was collected by means of a questionnaire. The method of data analysis used multiple regression analysis. The results of the research that obtained the Marketing Mix (Product, Price, Place, Promotion, Person or Staff, Process, Physical Evidence) had a positive and significant effect on sales simultaneously. While partially, the variables of the Marketing Mix (Product, Price, Place, Promotion, Person or Staff, Process, Physical Evidence) also have a positive and significant influence on sales in the manufacturing industry of PT. Dwiselaras Jayapack.